(3CLhHI eSGFd JJVef PcQ GdeWQajI hCMcGege hZjQ Pdcs - (3CHh eMeO YHO Gddg Hf MeRI Hf SdjeGf Hf MeRI GdMSfj Gdjefj,J (B614 (3g` s
(3ChdgG (B:s
(3EYde (B_ (3CjOc Gddg hgOGc Cf GdaQbI GdZhjI GdeSeGI HGdeWQajI bO LYdJ HYV GdPQjI GdWGgQI dgG HVGYI s
(3BNQgG (B:s
(3hCeG GdPi jMOK eY GdSHGjG ade JYde Pdc hGdJYRjR Ydi GdXf dGjLhR dCfg JbQjQ dhbhY GdNWHI , hde jJjbf hbhYgG hGdSdGe s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdahGJM HGdSejcs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B83s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3Gdabg GdESdGejs